Radioprotective effects of Antrodia cinnamomea are enhanced on immune cells and inhibited on cancer cells. (October 2014) - Cheng, Po-Ching; Huang, Chun-Chih; Chiang, Ping-Fang; Lin, Ching-Nan; Li, Li-Li; Lee, Te-Wei; Lin, Bin; Chen, I-Chen; Chang, Kang-Wei; Fan, Chia-Kwung; Luo, Tsai-Yueh
Abstract Purpose: The radioprotective effects of Antrodia cinnamomea (AC) were investigated for understanding the potential usefulness of AC as an adjunct treatment for reducing radiation side-effects. Materials and methods: In this study, we determined the ability of AC extracts (AC539) to reduce radiation side-effects by analyzing cellular viability in normal mouse spleen immune cells and human cancer cells with different radiosensitivity. We further detected the effect of AC on radiation-induced changes in cytokine- and inflammatory-related gene expressions. Furthermore, apoptosis assay was performed to determine whether AC could inhibit radiation-induced cytotoxicity. Results: We found that an AC dose of 100–150 μg/ml in a time-dependent manner was the most effective in blocking radiation-induced cytotoxicity, in vitro. Radiation-induced cytotoxicity was inhibited in spleen immune cells by 37–56%; however, pretreatment of human colorectal cancer cell line HT-29 with AC did not have any effect on radiation-induced cytotoxicity, while pretreatment of radiosensitive human breast cancer cell lines BT-474 with AC caused a moderate enhancement of radiation-induced damage. Furthermore, AC pretreatment differentially regulated the mRNA expression of several important immunomodulatory genes in response to irradiation in normal and cancer cells. Conclusions: Our data indicate that AC may inhibit important immunoregulatory signaling which could be vital in the avoidance of an over-activated cytotoxic and inflammatory response of the immune system caused by radiation-induced tissue damage. Additionally, AC does not provide a radioprotective effect to tumor cells but instead enhances radiation-induced inflammation and cytotoxicity in cancer.